You are on page 1of 24

KAIST
2004 9 25

, .
,
.

(Theorems)
1.1

|2A | = 2|A|

|U A| = |U | |A|
(De Morgans Law)
(A B)c = Ac B c

(p q) = p q

Ai

## (x, p(x)) x, p(x)

Aci

iI

iI

(Inclusion-Exclusion principle, - )
|A B| = |A| + |B| |A B|
|A B C| = |A| + |B| + |C| |A B| |A C| |B C| + |A B C|
n

i=1

(1)r+1

Ai =
r=1

Aij
i1 ,...,ir j=1
distinct

(Theorems)

p q

pq

(Mathematical Induction)
1S

nS n+1S

SN

(n N)

(Strong Induction)
1S

1, . . . , n S n + 1 S

SN

(n N)

- (Backward Induction)
|S| =

n+1S nS

SN

(n N)

( , Well-Ordering Principle)
=SN

(Pigeonhole Principle, )

1.2

## |P1 | + + |Pn | > n

p1 + + pn > m

p1 + + pn > r1 + + rn

> .

(Number Theory)

(1) a | b

a | bc

(2) a | b, a | c

a|b+c

(3) a | b, b | c

a|c

(4) a | b, b = 0

|a| |b|

m
pi >
(i)
n
pi > ri

(i)

## 1.2 (Number Theory)

(5) a | b, b | a

|a| = |b|

: a b > 0 q, r ()
a = bq + r

(0 r < b)

: d = gcd(a, b) ,
(1) d = min{ ax + by > 0 | x, y Z }
(2) gcd(ma, mb) = md
(3) a | bc

(3) a | c, b | c

a
d

(5) AB = GL

(m > 0)

|c
ab
d

|c

## (6) : gcd(a, b) = gcd(a + kb, b)

: , .

e
e
q = p11 pkk (ei Z) .

: n = pe11 pekk
(n ) = (e1 + 1) (ek + 1)
(n ) = (1 + p1 + + pe11 ) (1 + pk + + pekk )

(1) p | ab
(2) pk

p | a p | b
n
n
n
k =
+ 2 + 3 +
p
p
p

n!

(3) : .

gcd(a, b) = 1 an + b ,

(Dirichlet) .

(1) a b, b c (mod m)

a c (mod m)

(2) a b, c d (mod m)

a + c b + d (mod m)

(3) a b, c d (mod m)

ac bd (mod m)

(4) a b (mod m)

## p(a) p(b) (mod m)

(p )

(Theorems)

(5) ac bc (mod m)

a b (mod

m
d)

(d = gcd(c, m))

: ax + by = c (x0 , y0 )
.
(x, y) = (x0 , y0 ) + (a , b )t

(t Z)

, g = gcd(a, b), a = a g, b = b g g | c .
.

ax b (mod m)

gcd(a, m) | b

gcd(a, m) = 1 aa 1 (mod m) a .
:
f (x, y) 0 (mod n)

f (x, y) = 0

3 : a2 + b2 = c2 .
({a, b}, c) = ({(m2 n2 )r, 2mnr}, (m2 + n2 )r)

(m, n, r Z)

: mi

a
(mod
m
)

1
1

..
= A, x A (mod m1 mk )
.

x ak (mod mk )
A mod m1 mk .
,
n mod m 1 X mod m
, m n mod m
1 Y mod m .
(1) |X| = n, |Y | = (n)
(2) X + a := { x + a | x X }
(3) gcd(a, m) = 1 aX := { ax | x X } , aY

## 1.2 (Number Theory)

-
(1) gcd(a, b) = 1

(ab) = (a)(b)

## (2) (pk ) = pk pk1

(3) (n) = n
p|n

(p )

1
1
p

Fermet , Euler
ap1 1 (mod p)

(, p a, p )

a(n) 1 (mod n)

(, gcd(a, n) = 1)

Wilson
(p )

(p 1)! 1 (mod p)

## 2 (Quadratic Residue): mod m .

mod 3:

0, 1

mod 4:

0, 1

mod 5:

0, 1, 4

mod 7:

0, 1, 2, 4

mod 8:

0, 1, 4

mod 10:

0, 1, 4, 5, 6, 9

(Legendre)

1
a p 2
a
:=
1
p
(Legendre)
(1)

a
p

(2)

ab
p

(3)

1
p

= 1,

2
p

= (1)

(4)

p1
2

a
p

(mod p).
b
.
p

p 2 1
8

1
p
=

= (1)

p1
2

p 1 (mod 4)

1 p 3 (mod 4)
p 1 or 7 (mod 8)

1 p 3 or 5 (mod 8)

(Theorems)

(5) p, q ,
p
q

1.3

q
p

p 1 q 1 (mod 4)

1 p q 3 (mod 4)

(Algebra)

x3 + y 3 + z 3 3xyz = (x + y + z)(x2 + y 2 + z 2 yz zx xy)
x4 + x2 + 1 = (x2 + x + 1)(x2 x + 1)
(Remainder Theorem)
p(x) = (x a)q(x) + p(a)
(Factor Theorem)
p(a) = 0

(x a) | p(x)

## (Rational Root Theorem)

P (x) = an xn + an1 xn1 + + a1 x + a0 , gcd(r, s) = 1
P

s
=0
r

r | an , s | a0

(Identity Theorem)
n p p(x) = 0 n p .
(Fundamental Theorem of Algebra)
n n .
(Vieta )

x2 px + q = (x a)(x b)

p = a + b

q = ab
k

xn p1 xn1 + + (1)n pn = (x a1 ) (x an )

pk =

aij
i1 ,...,ik j=1
distinct

1.4 (Inequalities)

f (x1 , . . . , xn ) xi , xj
. p
. pk . ,
(P )

p = P (p1 , . . . , pk )

.
q . ,
(r)

(xi xj )

q(x1 , . . . , xn ) = r(x1 , . . . , xn )
i<j

(homogeneous equation)
{ x | Ax = b } = { x 0 + y | Ay = 0 }
, x 0 Ax = b .
(Gaussian Elimination)
A

A1 A = E A1 b = x .

1.4

(Inequalities)

x {x} := x x .
(1) x = x
(2) x + n = x + n

(n )

(3) x x = x + x = 1

## (4) x + y = x + y + {x} + {y}

x =
x
(5)
(6)

x
n

x
n

(n )

x =

(Theorems)

10

AB AC + CB
x +y x + y
: A B .
: a1 , . . . , an > 0 ( )

a 1 + + an
n a1 an
n

1
a1
1 + + an
n

a1 = = an .
:
a1 , . . . , an > 0 , 1 + + n = 1, 1 , . . . , n 0 , =
(1 , . . . , n ) x1 , . . . , xn p .
Mp, (a1 , . . . , an ) :=

1 ap1 + + n apn
n

1/p

(p = 0)

## M0, := limp0 Mp, = a1 1 ann Mp p .

p = 1 (), 1 = = n =

1
n

: a1 , . . . , an ; b1 , . . . , bn ,
b1 , . . . , bn b1 , . . . , bn
a1 b1 + + an bn a1 b1 + + an bn a1 bn + + an b1
(Tchebychefs Inequality): a1 , . . . , an ; b1 , . . . , bn

a1 b1 + + an bn
a1 + + an b1 + + bn
a1 bn + + an b1

n
n
n
n
(Cauchy-Schwarz Inequality)
(a21 + + a2n )(b21 + + b2n ) (a1 b1 + + an bn )2
a

b ab

( , Jensens Inequality): I f
x1 , . . . , xn I , x1 , . . . , xn f (x1 ), . . . , f (xn )
x, f (x) .

11

(1) f I ( )
(2) f I ( )

f (x) f (x)

=
=

f (x) f (x)

## (Schurs Inequality): x, y, z, n > 0

xn (x y)(x z) + y n (y z)(y x) + z n (z x)(z y) 0
(H
olders Inequality): ai , bj > 0 p + q = 1, p, q > 0
p

a1
b1

= =

an
bn

1
p

1
q

= 1, p, q > 0

## Mp (a1 , . . . , an )Mq (b1 , . . . , bn ) M1 (a1 b1 , . . . , an bn )

.
(Minkowskis Inequality): ai , bj > 0 p 1
Mp (a1 , . . . , an ) + Mp (b1 , . . . , bn ) Mp (a1 + b1 , . . . , an + bn )

1.5

## (Functions and Sequences)

k=
k=1
n

k2 =
k=1
n

k3 =
k=1
n1

rk =
k=0
n

k=1

1
=
k(k + 1)

n(n + 1)
2
n(n + 1)(2n + 1)
6
n(n + 1)
2

1 rn
1r
n

k=1

1
1

k k+1

=1

1
n+1

(Theorems)

12

p-
1
1 1
+ + + + =
2 3
n
1
1
1
1 + 2 + 2 + + 2 + < 2
2
3
n
1+

1
p > 1 , 0 < p 1 .
p
n
n=1

an pan1 + qan2 = 0
{an } .
an = c1 n + c2 n
, , x2 px + q = 0 , c1 , c2 a1 ,
a2 .

## i sin ) an = rn (c1 cos n + c2 sin n) .

(Fibonacci sequence): F0 = 0, F1 = 1, Fn = Fn1 + Fn2
{Fn }
1
Fn =
5

1+ 5
2

1 5
2

(1) Fn+1 Fn1 Fn2 = (1)n
(2) Fn+k = Fk Fn+1 + Fk1 Fn
(3) m | n

Fm | Fn

## (4) gcd(Fm , Fn ) = Fgcd(m,n)

(5) (Zeckendorf ) n
.
n = Fk1 + Fk2 + + Fkr
, i

k1

k2

j i j + 2 , r .

kr

## (1) p(z) = p(z)

13

(p)

(2) |z|2 = zz
(De Moivres Theorem)
(cos + i sin )n = cos n + i sin n
(ei )n = ein

cos(A + B) + i sin(A + B) = (cos A cos B + i2 sin A sin B) + i(cos A sin B + cos B sin A)
ei(A+B) = eiA eiB
1 n
zn = 1

z = ei2 n = cos 2

k
k
+ i sin 2
n
n

(k = 0, . . . , n 1)

(Intermediate-Value Theorem)
f I , a, b I (a < b)
f (a)f (b) < 0

## x (a, b), f (x) = 0

f (x + y) = f (x) + f (y)
f f (1) = a
f (x) = ax
.
(i) x N
(ii) x Z
(iii) x Q

x R f (x) = ax . , f

, .

(Theorems)

14

1.6

(Combinatorics)

f : A B

n r nr
a b
r

(a + b)n =
r=0

r=0

n
r

|A| = |B|

= 2n ,
r=0

n
(1)r = 0
r

(1)
(2)
(3)

n
n1
=
k
k1
m m
+
0
n
k
k+1
+
k
k

n1
k
m
m
m
+ +
1
n1
n
n
n+1
+ +
=
k
k+1
+

m
0

m+m
n

1
1
1
1
1
1

..
.

3
4

1
3
6

10

..
.

1
4

10

..
.

5
0

4
0

..
.

3
0
5
1

2
0
4
1

1
0
3
1
5
2

0
0
2
1
4
2

..
.

1
1
3
2
5
3

2
2
4
3

3
3
5
4

4
4

..
.

5
5

(x1 + + xk )n =
r1 ++rk =n
r1 ,...,rk 0

n
xr1 xrkk
r1 , . . . , rk 1

r1 ++rk =n
r1 ,...,rk 0

n
r1 , . . . , rk

= kn

(Permutation)
[n] := {1, 2, . . . , n} : [n] [n] [n]
. k i1 , i2 , . . . , ik
(i1 i2 ik i1 ) k-(cycle) (i1 i2 ik ) . 2-
, (transposition) .

1.6 (Combinatorics)

15

(Odd/Even Permutation)
() .
,
.
, .
(Derangement)
(n) = n n . [n]
Dn .
Dn = (n 1)(Dn1 + Dn2 )
n

Dn = n!
k=0

D0 = 1, D1 = 0

(1)k
k!

P (A B) = P (A) P (B | A)

(1) E(aX + b) = aE(X) + b
(2) E(X 2 ) = E(X)2 + V (X)
: .
(1) ( )
(2) 2 ( )
(Eulers Formula): , , v, e, f
ve+f =2
(Ramsey Theory)
Kr ,
Km Kn
. m, n , r .
r - R(m, n) .

(Theorems)

16

(Generating Funtion)
a0 , a1 , a2 , a3 , . . .
a0 + a1 x + a2 x2 + a3 x3 +

1
:= 1 + x + x2 + x3 + = (1 + x)(1 + x2 )(1 + x4 )(1 + x8 )
1x
1
x2
x3
log
:= x +
+
+
1x
2
3
x2
x3
ex := 1 + x +
+
+
2!
3!

1
Fn xn =
(Fn : )
1

x
x2
n=0

Hn xn =

1
1
log
1x
1x

Dn xn =

ex
1x

n=1

n=0

(Hn := 1 +

1 1
+ + )
2 3

(Dn : )

(Catalan Number)
Cn = C1 Cn1 + C2 Cn2 + + Cn1 C1
Cn =

1
2n
n+1 n

2n + 1
1
2n + 1
n

(2n)!
n! (n + 1)!

.
(1) 2n . , n ,
,
.
(2) n n AB
, A B .
(3) (n + 2) n .
(4) 2n 2 n ,
, .
(5) n (binary tree). ,
(root) (tree) (rooted tree) ,
(child, ) 0, 1, 2
.

1.7 (Geometry)

17

## (6) n + 1 (ordered tree). ,

.
(7) 2n + 1 - (full binary tree). ,
0 2 - .
(Stirling Number)
[n] k 1
s(n, k)

n
k

. [n] k 2

S(n, k)

n
k

n
n1
n1
=
+ (n 1)
k
k1
k
n
n1
n1
=
+k
k
k1
k

1.7

(Geometry)

: AD A , BA : AC = BD : DC
: AB, AC D, E DE

BC DE = 12 BC

: a, b < c a2 + b2 = c2
(Pappus): M BC AB 2 + AC 2 = 2(AM 2 + BM 2 )
:

ABCD .

(1) 180 . .

()

(3) P A P B = P C P D

(P = XY ZW )

(Ptolemy): ABCD
AB CD + BC AD = AC BD
: (), , , ,
(1) .
(2) .
.

(Theorems)

18

(3) 2 : 1 .
(rA , rB , rC )
1
1
1
1
+
+
=
r
rA rB
rC
OI 2 = R2 2Rr
(Apollonius)
A, B m : n , AB m : n
P , Q P Q .

F , AF B =
BF C = CF A = 120 .
: , ,
.
(Simpson): ( )
.

a = 2R sin A

sin A
a
=
b
sin B

2
b2 + c2 a2
2ab
1
AB AC = (AB 2 + AC 2 BC 2 )
2
cos A =

2bc cos A
2
b+c

1
1
ah = ab sin C
2
2
(2) S = sr = (s a)rA = s(s a)(s b)(s c)
a2 sin B sin C
abc
= 2R2 sin A sin B sin C = Ra sin B sin C =
(3) S =
4R
2
sin A
(1) S =

1.7 (Geometry)

19

(1) a, b a b .
(2) a, b, c ax = bc x .
: 1 1
.
:
.
- (Mascheroni-Mohr):
.
: , , .
: .
: / .

ab = a
=a

b cos
b + a b 0

(x1 , . . . , xn ) (x1 , . . . , xn ) = x1 x1 + + xn xn
: (x1 , y1 ), (x2 , y2 ), (x3 , y3 )
S=

x1

x2

x3

x1

y1

y2

y3

y1

:= (x1 y2 + x2 y3 + x3 y1 ) (x2 y1 + x3 y2 + x1 y3 )

(a b) c =

c =

ab
b
b b

: p v (x a) = 0
d = (p a)

|v (p a)|
v

(Theorems)

20

## (Ceva): D, E, F BC, CA, AB( ) , AD,

BE, CF
DB EC F A

= 1
DC EA F B
(Menelaus): D, E, F BC, CA, AB( )
, D, E, F
DB EC F A

=1
DC EA F B
(Desargue)
AA , BB , CC ABC A B C ,
D = BC B C , E = CA C A , F = AB A B , (
) D, E, F .
(Pascal)
A, B, C, A , B , C , D = BC
B C , E = CA C A , F = AB A B , ( ) D, E,
F .

3 A, , , A
H , A H .
Prismatoid : A, B
M , h .
V =

1
(A + 4M + B)h
6

O, r O , OA OA OA = r2 A
O A . .

(Notation and Symbols)

pq

p q

pq

p q

pq

p q; p q

x( A), p(x)

x( A) p(x)

x( A), p(x)

x( A) p(x)

!x

p(x) q(x)

## p(x) q(x) ; (x) p(x) q(x)

p(x) q(x)

p q ; p(x) q(x)

xA

x A

AB

A B

AB

AB

AB

; A B c

Ac

; U A

|A|

2A

A , A

(Theorems)

22

AB
p

, a A, b B (a, b)
(p)

pq

(p q)

p+q

(p q)

pq

; (p + q)pq

a|b
pk

a b ; t Z, b = at
pk n ; pk | n pk+1 n

gcd(a, b)

, (a, b)

lcm(a, b)

, [a, b]

a b (mod m)
(n)
a
p

, a b m ; m | a b
-, n n
; a mod p 1, 1

ai

ai

|x|

, x ; , [x]

iI

iI

1.7 (Geometry)

23

, x

; 2.718182

loga x

sin x

(sine)

cos x

(cosine)

tan x

(tangent)

eix
z

cos x + i sin x

Re z

Im z

n!
n
r
n
r1 , . . . , rk
[n]
P (X)
P (A | B)

(factorial); 1 2 n
n!
;
r! (n r)!
n!
(r1 , . . . , rk 0, r1 + + rk = n)
;
r1 ! rk !
{1, 2, . . . , n}

E(X)

V (X)

(X)

AB

AB

AB
m

, ; AB, |AB|

(Theorems)

24

ABC

DEF

ABC

DEF

; x

; (a1 , . . . , an ) =

a
ab

; (a1 , . . . , an ) (b1 , . . . , bn ) = a1 b1 + + an bn

a b

a b

a b

a21 + + a2n

; det A